Simulação numérica do processo de secagem de concretos refratários em aplicações tecnológicas - Cunha, Túlio Mumic (Universidade Federal de São Carlos, 2022)
Refractory ceramics are used in high temperatures due to their unique properties that enable a high thermal and chemical stability, mechanical strength, thermal properties and others. These materials are split into two main groups: shaped and monolithic. The latter acquires its shape during application and is commonly obtained as a powder, to which a liquid, commonly water, is added for mixing and for reacting with the binding agents to guarantee suitable green strength. Following, it is subjected to careful heating schedule to withdraw this water, because rapid generation of steam can lead to the failure of the lining. The drying process is often approached empirically in the industry, and this work aims to introduce a computational methodology for comparison and optimization of such heating profiles. Initially, a finite element method modeling was developed, with the help of a library, in Python, which was the basis for a number of simulations that were divided into three stages: profiles with constant heating rate, others with a plateau and also complex curves. The analyzes showed the need to use properties as a function of temperature, so it is as close as possible to a real material; high heating rates (≥ 50°C/h) are viable for linings with small thickness (< 20 cm); the withdrawal of free water at plateaus with temperatures below, but close to, the temperature of the beginning of the hydrate decomposition process enables the use of short plateaus at higher temperatures, speeding the drying process. Finally, using indicators such as drying status, resistance ratio and energy consumption, it was possible to compare the curves with each other to choose the one that best meets the needs of the end-user.
Numerical simulation of the drying process of refractable castables in technological applications
Keywords: Concreto refratário; Secagem; Otimização; Simulação numérica; Refractory concrete; Drying; Optimization; Numerical simulation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS